Long-Term Efficacy of Neoadjuvant Concurrent Chemoradiotherapy for Potentially Resectable Advanced Siewert Type II and III Adenocarcinomas of the Esophagogastric Junction - Tian, Yuan; Wang, Jun; Qiao, Xueying; Zhang, Jun; Li, Yong; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; Tan, Bibo; Wang, Dong; Yang, Peigang; Zhao, Qun (Frontiers in Oncology, 2021)
Background Reports have shown that neoadjuvant concurrent chemoradiotherapy (nCRT) increases the R0 resection rate for patients with Siewert type II or III adenocarcinoma of the gastroesophageal junction (AEG). However, the long-term efficacy of nCRT for AEG patients remains unclear. In this multicenter study, we investigated the long-term results of AEG patients treated with nCRT. Methods A total of 149 patients with potentially resectable advanced AEG (T3/4, Nany, M0) were randomly divided into two groups: the nCRT-treated group (treated group) (n = 76) and the surgery group (control group) (n = 73). The primary endpoint was disease-free survival (DFS), and the secondary outcome indexes included the R0 resection rate, HER-2 expression, tumor regression grade (TRG), objective response rate (ORR), disease control rate (DCR), overall survival (OS), and adverse events. Results In the treated group, the overall therapeutic efficacy rate was 40.8%, and the pathological complete response (pCR) rate was 16.9%. The rates of patients who underwent R0 resection in the treated and control groups were 97.0% and 87.7%, respectively (p < 0.05). The toxic effects were mainly graded 1–2 in the treated group. The median DFS times in the treated and control groups were 33 and 27 months, respectively (p = 0.08), whereas the median OS times were 39 and 30 months, respectively (p = 0.01). The median DFS times of patients with positive and negative HER-2 expression in the treated group were 13 and 43 months, respectively (p = 0.01), and the median OS times were 27 and 41 months, respectively (p = 0.01). Conclusion Surgery after nCRT improved the efficacy of treatment for AEG patients and thus provided a better prognosis. Clinical Trial Registration The trial is registered with ClinicalTrials.gov (number NCT01962246).